Tools for living a sourcebook of iconic designs for the home - Fiell, Charlotte (Fiell Publishing, 2010)
Tools For Living' is a book all about 'ultimates' - the ultimate things designed for the home - from chef knives and pots and pans, to door handles and bathroom taps, to home-office furniture and garden tools.